2015
DOI: 10.1515/zpch-2015-0603
|View full text |Cite
|
Sign up to set email alerts
|

Can we Observe Gas Phase Nucleation at the Molecular Level?

Abstract: We propose and discuss an experiment for the study of neutral gas phase nucleation on a molecular level using propane as the condensable gas. The experiment combines a uniform Laval expansion with soft mass spectrometric detection. The uniform Laval expansion allows nucleation experiments under welldefined conditions while the mass spectrometric detection provides molecularlevel information on the molecular aggregates formed. It is discussed how one could observe the onset of nucleation and retrieve the size o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 38 publications
2
26
0
Order By: Relevance
“…12 Furthermore, to avoid saturation effects caused by the monomer in the cluster measurements, the monomer ion was selectively deflected by a pulsed plate located in front of the MCP detector for the cluster measurements. 10,11,13…”
Section: A Instrumentationmentioning
confidence: 99%
See 3 more Smart Citations
“…12 Furthermore, to avoid saturation effects caused by the monomer in the cluster measurements, the monomer ion was selectively deflected by a pulsed plate located in front of the MCP detector for the cluster measurements. 10,11,13…”
Section: A Instrumentationmentioning
confidence: 99%
“…The present work reports the first laboratory measurements of water nucleation to provide direct molecular level information such as critical cluster sizes at temperatures below 87 K. This is achieved by monitoring cluster size distributions during nucleation in the uniform postnozzle flow of a Laval expansion [10][11][12][13] with mass spectrometry after single-photon vacuum ultraviolet (VUV) ionization. [14][15][16][17] It has recently been shown that in contrast to electron ionization, singlephoton vacuum ultraviolet ionization close to the threshold is a soft ionization method even for weakly bound molecular clusters.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…By applying high ion extraction voltages, they are able to observe cluster distributions [253][254][255] that include the monomer, dimer, trimer, etc., through to particles with diameters between 10 and 20 nm. As illustrated in Fig.…”
Section: Following Nucleation In Systems With Weakly Bound Clustersmentioning
confidence: 99%